2001
DOI: 10.1002/1520-6807(200101)38:1<43::aid-pits5>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Multiple perceptions of children's aggression: Differences across neighborhood, age, gender, and perceiver

Abstract: We investigated how overtly aggressive behavior was differentially perceived by two types of perceivers, teachers and peers, as a function of student neighborhood, gender, and grade level. Participants (N ϭ 765) were predominantly African American students in grades 3 -5 recruited from two urban public schools in southern California. The neighborhoods surrounding the two schools differed in levels of identified violent crime and economic levels. Teachers in the community experiencing more violence perceived st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Research suggests that parents living in violent neighborhoods may be less likely to try to reduce adolescents’ aggressive behavior because they believe that aggressive behavior is necessary for adolescents to defend themselves (Duncan, Brooks-Gunn, & Klebanov, 1994); instead, parents may communicate the value of aggressive behavior as protective against exposure to community violence regardless of their child’s gender; if so, males and females exposed to community violence might display similar aggressive behaviors. Relatedly, aggressive behaviors may be perceived as normative in violent contexts and girls and boys may display similar levels and types of aggression in these settings (e.g., Hudley et al, 2001; McMahon, Felix, Halpert, & Petropoulos, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that parents living in violent neighborhoods may be less likely to try to reduce adolescents’ aggressive behavior because they believe that aggressive behavior is necessary for adolescents to defend themselves (Duncan, Brooks-Gunn, & Klebanov, 1994); instead, parents may communicate the value of aggressive behavior as protective against exposure to community violence regardless of their child’s gender; if so, males and females exposed to community violence might display similar aggressive behaviors. Relatedly, aggressive behaviors may be perceived as normative in violent contexts and girls and boys may display similar levels and types of aggression in these settings (e.g., Hudley et al, 2001; McMahon, Felix, Halpert, & Petropoulos, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…For example, research has suggested that gender differences in aggressive behavior may emerge because the greater visibility of boys' behavior compared with that of girls leads teachers to report boys' aggressive behavior more frequently [12]. Although studies have not considered the role of teacher reports on results of gender differences in prosocial behavior, it is possible that a similar relationship exists in the present study, where boys display more visible acts of prosocial behavior than girls, or that teacher reports are influenced by gender-related expectations.…”
Section: Discussionmentioning
confidence: 99%
“…The need to address the problem has taxed the resources of schools and translated into initiatives that extend work responsibilities for teachers and administrators. Although there seems to be a clear mandate to do something, how educators identify incidents as violent and decide to respond to them remains underexamined yet likely varied and contradictory (see Astor, Behre, Fravil, & Wallace, 1997;Ayers, Dohrn, & Ayers, 2001;Hazler, Miller, Carney, & Green, 2001;Hudley et al, 2001;Noguera, 1995). More so, as educators go about the work of identifying and responding to violence, they engage in socalled discursive practice, applying ideologically based terms and meanings to render some behaviors and bodies violent and not others.…”
mentioning
confidence: 99%